TRANSLATION HYPERSURFACES WITH CONSTANT CURVATURE IN 4-DIMENSIONAL ISOTROPIC SPACE - Aydin, Muhittin Evren; Ogrenmis, Alper Osman (Bayram Sahin, 2019)
In the present study, we deal with translation hypersurfaces in the 4-dimensional isotropic space I4 generated by translating planar curves. Due to absolute figure of I4 there are four different types of such hypersurfaces. We classify these translation hypersufaces in I4 with constant Gauss-Kronecker and mean curvature. © 2019, Bayram Sahin. All rights reserved.
Keywords: Gauss-Kronecker curvature; isotropic space; mean curvature; Translation hypersurface